Measuring User Experience Inclusivity in Human-AI Interaction via Five User Problem-Solving Styles - Anderson, Andrew; Guevara, Jimena Noa; Moussaoui, Fatima; Li, Tianyi; Vorvoreanu, Mihaela; Burnett, Margaret (ACM Transactions on Interactive Intelligent Systems, 2024)
Motivations: Recent research has emerged on generally how to improve AI products’ human-AI interaction (HAI) user experience (UX), but relatively little is known about HAI-UX inclusivity. For example, what kinds of users are supported, and who are left out? What product changes would make it more inclusive? Objectives: To help fill this gap, we present an approach to measuring what kinds of diverse users an AI product leaves out and how to act upon that knowledge. To bring actionability to the results, the approach focuses on users’ problem-solving diversity. Thus, our specific objectives were (1) to show how the measure can reveal which participants with diverse problem-solving styles were left behind in a set of AI products and (2) to relate participants’ problem-solving diversity to their demographic diversity, specifically gender and age. Methods: We performed 18 experiments, discarding two that failed manipulation checks. Each experiment was a 22 factorial experiment with online participants, comparing two AI products: one deliberately violating 1 of 18 HAI guidelines and the other applying the same guideline. For our first objective, we used our measure to analyze how much each AI product gained/lost HAI-UX inclusivity compared to its counterpart, where inclusivity meant supportiveness to participants with particular problem-solving styles. For our second objective, we analyzed how participants’ problem-solving styles aligned with their gender identities and ages. Results and Implications: Participants’ diverse problem-solving styles revealed six types of inclusivity results: (1) the AI products that followed an HAI guideline were almost always more inclusive across diversity of problem-solving styles than the products that did not follow that guideline—but “who” got most of the inclusivity varied widely by guideline and by problem-solving style; (2) when an AI product had risk implications, four variables’ values varied in tandem: participants’ feelings of control, their (lack of) suspicion, their trust in the product, and their certainty while using the product; (3) the more control an AI product offered users, the more inclusive it was; (4) whether an AI product was learning from “my” data or other people’s affected how inclusive that product was; (5) participants’ problem-solving styles skewed differently by gender and age group; and (6) almost all of the results suggested actions that HAI practitioners could take to improve their products’ inclusivity further. Together, these results suggest that a key to improving the demographic inclusivity of an AI product (e.g., across a wide range of genders, ages) can often be obtained by improving the product’s support of diverse problem-solving styles.